EVALUATION OF BIM INTEROPERABILITY FOR STRUCTURAL ANALYSIS AND DESIGN OF MULTI-STOREY BUILDINGS - Syaiful Huda; Tira Roesdiana (LPPM Universitas Negeri Jakarta, 2025)
Interoperability between software platforms represents a significant challenge in Building Information Modeling (BIM) implementation for structural design and analysis of multi-storey buildings. This research evaluates the effectiveness of BIM interoperability between Autodesk Revit and ETABS through a case study of a four-story office building with Special Moment Resisting Frame System (SMRFS) located in Jakarta, Indonesia. Structural model transfer was performed from Revit to ETABS using CSiXRevit plugin with EXR format, followed by evaluation of data consistency in bidirectional transfer processes. Results demonstrate that initial transfer from Revit to ETABS successfully maintained all major structural parameters, although support type changes from fixed to pinned occurred requiring manual correction. In the reverse transfer from ETABS to Revit, data inconsistencies were found including 10% reduction in column dimensions (from 500×500 mm to 500×450 mm) and inaccuracies in reinforcement placement. The structural model successfully meets seismic requirements according to SNI 1726:2019 for mass participation parameters, base shear forces, and story drift. This research confirms that while EXR format can maintain relatively good structural data integrity, validation and manual corrections remain necessary to ensure model consistency in integrated BIM workflows.